Analisis Pemanfaatan Tumbuhan Obat oleh Masyarakat Plosorejo, Indonesia: Analysis of Medicinal Plant Utilization by the Plosorejo Community, Indonesia - Galuh Masyithoh; Maygita Serli Oktavia; Ana Agustina (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2026)
Ethnobotany is a branch of science that traditionally studies the interaction between humans and plants. One area of ethnobotany is the use of medicinal plants. People who utilize plants as medicine have an essential role in maintaining and preserving the diversity of these plants. This study aims to determine the types of medicinal plants used by the community and their conservation status in Plosorejo Village. The data collection method is purposive snowball sampling. Data collection was conducted through interviews with 18 informants, namely, people who use medicinal plants. Types, organs, processing methods, and ways of using medicinal plants are expressed as percentages, while the Species Use Value (SUV) is calculated by comparing the number of plant species with the number of informants. The study's findings revealed 37 medicinal plant species, belonging to 25 families. The SUV calculations showed that ginger (Zingiber officinale), the most valuable plant species, had the highest utility value, with an SUV of 1. The most widely used plant habitus is herbaceous (57.89%). The most commonly used way of using medicinal plants is drinking (68.85%). Based on the IUCN, the conservation status of medicinal plants includes least concern (21.62%), data deficient (16.22%), and not evaluated (62.16%). In order to safeguard medicinal plants, the community of Plosorejo Village must implement conservation measures. Effective maintenance of household gardens is a crucial community contribution and role that promotes food security, sustainability, and development.